Saint Irénée dans l'œuvre du P. de Lubac: Émergence d'un Docteur de l'unité - Lemaire, Marie-Gabrielle (Revue théologique de Louvain, 2023)
Irenaeus of Lyon, Father of the Church who died around 202, was only proclaimed Doctor of the Church on January 21, 2022, with the title of Doctor unitatis which underlines his role as a «spiritual bridge» between the East and the West. But he also deserves this title on the doctrinal level. By looking at the use made by Fr. Henri de Lubac of the writings of Irenaeus, we discover both a unified theology and a doctrine of the unity of the Church. The teaching of Saint Irenaeus binds together the mysteries of the faith in a view that embraces the dimensions of the Universe and of the History of the world from the origins, as we show through some salient points of his thought.